(untitled) (Gestão & Regionalidade, 2024)
The objective of this study was to map and investigate the development and structure of social networks of scientific production on the Balanced Scorecard theme published in Brazilian national scientific journals indexed in the Scientific Periodicals Electronic Library (SPELL). Methodologically, this research appropriated the techniques of Social Network Analysis from the perspectives of one-mode and two-mode social network analysis. The main results were: Sérgio Murilo Petri was the most prolific author and with the highest degree; the Federal University of Santa Catarina was the most productive, and stood out in the centrality of degree; the Electronic Journal of Strategy & Business was the most central scientific journal; the keywords: strategic planning, strategy, performance indicators, performance evaluation and strategic management, were the ones that had the most importance in the degree; and the themes most addressed by the authors were: strategic management, performance indicators, public management, strategic planning and performance evaluation.